PENGARUH PDRB, JUMLAH PENDUDUK, JUMLAH HOTEL, PENGELUARAN PEMERINTAH DAN INFLASI TERHADAP PENDAPATAN ASLI DAERAH (Studi Pada Kabupaten/Kota Provinsi Jawa Tengah Tahun 2011-2013) - Endrix Wibowo, 12.05.52.0165; Maryono, Maryono (Students Journal of Accounting and Banking, 2016)
This study aims to examine the effect of GDP, Population, Total Hotel, Expenditures and Inflation of the Revenue District / City in Central Java provinceÂ Years 2011-2013. The data used is the GDP, Population, Total Hotel, Expenditures and Inflation Local Revenue and the Regency / City Central Java. 105 samples obtained data. The research data were then tested by multiple linear regression.Â The results showed that: GDP positive and significant impact on the Local Revenue. Population and significant negative effect on local revenue. Hotel positive and significant impact on the Local Revenue. Spending positive and significant impact on the Local Revenue. Inflation is not a significant positive effect on local revenue.Keywords: GDP, Population, Total Hotel, Government Spending, Inflation, Local Revenue